Up to What Extent Does Dravet Syndrome Benefit From Neurostimulation Techniques? - Ding, Jiangwei; Wang, Lei; Li, Wenchao; Wang, Yangyang; Jiang, Shucai; Xiao, Lifei; Zhu, Changliang; Hao, Xiaoyan; Zhao, Jiali; Kong, Xuerui; Wang, Ziqin; Lu, Guangyuan; et al. (Frontiers in Neurology, 2022)
Background: Dravet syndrome (DS) is a refractory developmental and epileptic encephalopathy(EE) with a variety of comorbidities, including cognitive impairment, autism-like behavior, speech dysfunction, and ataxia, which can seriously affect the quality of life of patients and impose a great burden on society and their families. Currently, the pharmacological therapy is patient dependent and may work or not. Neuromodulation techniques, including vagus nerve stimulation (VNS), deep brain stimulation (DBS), transcranial magnetic stimulation (TMS), responsive neurostimulation (RNS), and chronic subthreshold cortical stimulation (CSCS), have become common adjuvant therapies for neurological diseases, but their efficacy in the treatment of DS is unknown. Methods: We searched Web of Science, PubMed, and SpringerLink for all published cases related to the neuromodulation techniques of DS until January 15, 2022. The systematic review was supplemented with relevant articles from the references. The results reported by each study were summarized narratively. Results: The Web of science, PubMed and SpringerLink search yielded 258 items. A total of 16 studies published between 2016 and 2021 met the final inclusion criteria. Overall, 16 articles (109 cases) were included in this study, among which fifteen (107 patients) were involved VNS, and one (2 patients) was involved DBS. After VNS implantation, seizures were reduced to≥50% in 60 cases (56%), seizure free were found in 8 cases (7.5%). Only two DS patients received DBS treatment, and the initial outcomes of DBS implantation were unsatisfactory. The seizures significantly improved over time for both DBS patients after the addition of antiepileptic drugs. Conclusion: More than half of the DS patients benefited from VNS, and VNS may be effective in the treatment of DS. However, it is important to note that VNS does not guarantee improvement of seizures, and there is a risk of infection and subsequent device failure. Although DBS is a safe and effective strategy for the treatment of refractory epilepsy, the role of DBS in DS needs further study, as the sample size was small. Thus far, there is no strong evidence for the role of DBS in DS.